Determinants of childcare service demand for infants aged 0–3 among the childbearing population in China - Yang, Chun; Zhou, Jian; Liu, Yan; Shi, Wenhui; Cheng, Yan; Cao, Yuxin; Xing, Rui; Cui, Lin; Liu, Rugang (Frontiers in Public Health, 2025)
ObjectivesThis study aims to investigate the demand for childcare services for infants aged 0–3 years among the childbearing population in China and identify its key determinants.MethodsAn online survey was conducted in Suzhou, China in August 2024 using a self-designed questionnaire. Information on personal and family characteristics, as well as demand for childcare services, was collected. Descriptive statistics, chi-square tests, and binary logistic regression were used to analyze the determinants of childcare services.ResultsOf 5,567 respondents, 45.9% expressed demand for childcare services for children aged 0–3 years. Binary logistic regression identified several significant predictors of demand. Notably, female gender, older age, rural residence, and lower educational attainment were associated with lower demand (p < 0.05). Conversely, having more children, greater trust in childcare institutions, better knowledge about childcare services, and greater awareness of childcare policies were significantly associated with higher demand (p < 0.05).ConclusionDemand for childcare services was influenced by multiple factors. Enhancing subsidies and rural service accessibility, strengthening institutional credibility, implementing incentives for multi-child families, disseminating childcare knowledge and policy information and facilitating a childcare paradigm shift were recommended.